Motivation and difficulties to reduce or quit smoking - Maria Odete Pereira; Bianca Cristina Silva de Assis; Natália de Magalhães Ribeiro Gomes; Alisson Rubson Alves; Amanda Márcia dos Santos Reinaldo; Mark Anthony Beinner (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To understand what factors motivate people to reduce or stop tobacco use and what difficulties they face in this process. Method: Qualitative, empirical and interpretative research that used a focal group technique for data collection and Discourse Analysis as a theoretical reference for analysis. Results: The responses centered on the following aspects: motivation for reduction or cessation of smoking, family and community support received during treatment, benefits from cessation of tobacco, difficulties encountered and strategies for overcoming triggers. Final Considerations: The results showed that the users expressed their desire for cessation of tobacco use and that to achieve this goal, family and group support, professional help and changing habits are key factors for this process.